Effective Homogeneous Hydrolysis of Phosphodiester and DNA Cleavage by Chitosan-copper Complex - 张琦 相艳 杨汝新 司江菊 郭红 (Chinese journal of chemistry, 2011)
We aimed to explore the role of chitosan-based metal complexes in catalyzing the hydrolysis of phosphodiesters To this end, we performed detailed studies on the kinetics of the chitosan copper complex （CSCu）-catalyzed hydrolysis of bis（4-nitrophenol） phosphate （BNPP） in Tris-H＋ buffer and in an organic solvent. A significant enhancement in the rate of reaction （up to 3 X 105-fold acceleration） was observed at pH 8.0 （25 ℃）. The pH depend- ence of BNPP hydrolysis at pH 5.5-9.5 and the UV spectra revealed that the copper-bounded water molecules un- derwent deprotonation to form the active catalytic species CSCu-OH. The kinetic behavior of BNPP catalytic hydrolysis in the Tris-H＋ buffer was consistent with that predicted by the Michaelis-Menten kinetics model. An in-ramolecular nucleophilic attack by the copper-bonded hydroxide group on the same activated phosphodiester substrate was proposed as the catalytic mechanism for CSCu-catalyzed reaction system. The results of DNA binding and cleavage experiments indicated electrostatic binding mode of CSCu to DNA as well as the strong capability of CSCu to disturb the supercoiled strand of DNA and cleave it to nicked circular form.